2019
DOI: 10.3390/ijms20030740
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Toxicity of Industrially Relevant Silicomanganese Dust on Human 1321N1 Astrocytoma Cells: An In Vitro Study

Abstract: Tremendous efforts are applied in the ferroalloy industry to control and reduce exposure to dust generated during the production process, as inhalable Mn-containing particulate matter has been linked to neurodegenerative diseases. This study aimed to investigate the toxicity and biological effects of dust particles from laboratory-scale processes where molten silicomanganese (SiMn) was exposed to air, using a human astrocytoma cell line, 1321N1, as model system. Characterization of the dust indicated presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…2 The silicomanganese is one of them and known in the literature as SMFs. 3 8 The SMF is reported by several other researchers as a byproduct of the steelmaking industry. 6 , 9 , 10 In Spain, waste generation of the steelmaking industry is 15 to 20% of the production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The silicomanganese is one of them and known in the literature as SMFs. 3 8 The SMF is reported by several other researchers as a byproduct of the steelmaking industry. 6 , 9 , 10 In Spain, waste generation of the steelmaking industry is 15 to 20% of the production.…”
Section: Introductionmentioning
confidence: 99%
“…During the entire steelmaking process, several byproducts are generated such as blast furnace slag, steelmaking slag, fly ash, blast furnace clarifier sludges, blast furnace flue dust, mill scales, waste refractories, coke breeze, and silicomanganese fumes (SMFs) . The silicomanganese is one of them and known in the literature as SMFs. The SMF is reported by several other researchers as a byproduct of the steelmaking industry. ,, In Spain, waste generation of the steelmaking industry is 15 to 20% of the production . In European Union, 22 million tons of slags were generated in 2010, and the majority of the waste generated was utilized as a landfill .…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes, a type of multifunctional cell and active communication partners, form an integral part of the blood–brain barrier, contributing to protecting the brain from toxic metabolites and peripheral insults . Studies have found that quiescent astrocytes are activated, referred to as reactive astrocytes, in response to a variety of neural damages in the central nervous system .…”
Section: Introductionmentioning
confidence: 99%